SIRT1 inhibits adipogenesis and promotes myogenic differentiation in C3H10T1/2 pluripotent cells by regulating Wnt signaling. Issue 1 (December 2015) - Zhou, Yuanfei; Zhou, Zheng; Zhang, Wei; Hu, Xiaoming; Wei, Hongkui; Peng, Jian; Jiang, Siwen
Abstract Background The directed differentiation of mesenchymal stem cells (MSCs) is tightly controlled by a complex network. Wnt signaling pathways have an important function in controlling the fate of MSCs. However, the mechanism through which Wnt/β-catenin signaling is regulated in differentiation of MSCs remains unknown. SIRT1 plays an important role in the regulation of MSCs differentiation. Results This study aimed to determine the effect of sirtuin 1 (SIRT1) on adipogenesis and myogenic differentiation of C3H10T1/2 cells. First, the MSC commitment and differentiation model was established by using 5-azacytidine. Using the established model, C3H10T1/2 cells were treated with SIRT1 activator/inhibitor during differentiation. The results showed that resveratrol inhibits adipogenic differentiation and improves myogenic differentiation, whereas nicotinamide promotes adipogenic differentiation. Notably, during commitment, resveratrol blocked adipocyte formation and promoted myotubes differentiation, whereas nicotinamide enhanced adipogenic potential of C3H10T1/2 cells. Furthermore, resveratrol elevated the expression of Cyclin D1 and β-catenin in the early stages. The luciferase assay showed that knockdownSIRT1 inhibits Wnt/β-catenin signaling, while resveratrol treatment or overexpressionSIRT1 activates Wnt/β-catenin signaling. SIRT1 suppressed the expression of Wnt signaling antagonistssFRP2 andDACT1 . KnockdownSIRT1 promoted adipogenic potential of C3H10T1/2 cells, whereas overexpressionSIRT1 inhibited adipogenic differentiation and promoted myogenic differentiation. Conclusions Together, our results suggested that SIRT1 inhibits adipogenesis and stimulates myogenic differentiation by activating Wnt signaling.